CHANGES OF SUCROSE CONTENT AND INVERTASE ACTIVITY DURING SUGARCANE STEM STORAGE - Tri Agus Siswoyo; Ika Oktavianawati; Djenal Djenal; Bambang Sugiharto; Untung Murdiyanto (Indonesian Agency for Agricultural Research and Development, 2007)
Invertases (beta-D-fructofuranosidase, E.C. 3.2.1.26) are the key enzymes involved in sucrose metabolism in sugarcane plants. They are highly correlated with sucrose and reducing sugar contents during plant growth. The sugarcane plants have two kinds of invertases, namely neutral invertase (NI) and acid invertase (AI). They have different function in sucrose accumulation. The research aimed to study the role of AI and NI in accumulation of reducing sugar during storage of sugarcane stems. Plant materials of 18-month-old field grown sugarcane of the commercial variety R-579 (wet-land) and M 442-51 (dry-land) were used. Three internodes were sampled to represent immature (internode 1-8/F1), maturing (internode 9-16/F2), and mature (internode 17-24/F3) stem tissues. All tissues were stored for 0-9 days at room temperature (28-32oC) and each day, the samplewas extracted to determine invertase activity, total soluble protein, and sugar contents. This observation was valid for invertase activity expressed on a protein basis. At the initiateharvested (0-3 days), NI had a higher specific activity than AI in the sucrose-accumulating region of the sugarcane stems. Negative significant correlation was found between NI specific activity and sucrose accumulation (r2 = 0.41, P < 0.05). AI showed a higher specific activity after 4 days harvested and had negative correlation with sucrose accumulation (r2 = 0.40, P < 0.05). These results showed that NI could be more responsible in sucrose hydrolisis than AI at early storage of sugarcane stems.